Efforts to Implement a Reward System (Incentives, Promotions, and Career Development) to Improve the Performance of Nurses - Darmawati Abdul Rachman; Yuly Peristiowati; Rahmania Ambarika (Health and Technology Journal (HTechJ), 2025)
The working conditions of healthcare workers in Indonesia, especially in state hospitals, remain unsatisfactory. One factor that influences this is the low reward system in state hospitals compared to private hospitals. The purpose of this research is to determine the effect of the reward system (incentives, promotions, and career development) on improving the performance of nurses. The design of this research is quantitative, employing a cross-sectional approach, with the population in this study comprising all 150 nurses at UPTD RSUD Bobong. The sample consisted of a portion of the population that met the inclusion criteria, comprising 112 people selected using a simple random sampling technique. The collected data were analyzed using Spearman's rho statistical test and ordinal logistic regression analysis with an α error rate of 0.05. The results of the analysis using the ordinal regression test yielded a significant result. (2-tailed) values ​​for the incentive factor (p-value = 0.012 < 0.05), promotion factor (p-value = 0.023 < 0.05) and career development factor (p-value = 0.019 < 0.05). The research shows that incentive, promotion, and career resulted in harm er development factors in implementing the reward system influence the performance of nurses at Bobong Hospital, Taliabu Island Regency. The incentives factor is the most dominant in the reward system, which influences nurse performance.